Analysis on Nylon 6/6 Camshaft Gear Temperature Simulation In A 1.1 Kva Elepaq Generator Using Inventor and ANSYS - Sanni, Olalekan Abdulrahim; Oke, Sunday Ayoola (International Journal of Mechanical Engineering Technologies and Applications, 2021)
Camshaft gear temperature simulations are presently crucial as they offer a distinctive visual account of the temperature profile within the generator, they permit superior manufacturing assessment and the design of heat-resistant camshaft gear with high performance and low cost. However, available information to designers is inadequate as they omit the approximate global maximum temperature, particularly for the nylon 6/6 camshaft gear in a 1.1 kVA elepaq generator. In this article, the idea is to simulate and account for the global minimum and maximum temperature using the Inventor and ANSYS software. The stress-induced on the generator was considered. The results of the simulation revealed an approximate global maximum temperature of the nylon 6/6 camshaft gear as 37°C max with 22°C min. Furthermore, the global minimum at 35°C max with 21°C min was considered. Besides, the structural steel global maximum of 38°C max, 25°C min and global minimum 35°C max, 24°C min. The stress values did not exceed 0.1419 MPa on ANSYS but the ANSYS revealed that the camshaft gear strain was within safe limits. The simulation approach predicts the minimum and maximum temperature of the nylon 6/6 camshaft gear and the stress and strain values. The utility of this attempt is to help designers to implement effective decisions on material choice and design parameters for optimisation, performance and low-cost design.